2019
DOI: 10.1371/journal.pone.0219677
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature and water turbulence on vertebral number and body shape in Astyanax mexicanus (Teleostei: Characidae)

Abstract: Environmental changes can modify the phenotypic characteristics of populations, which in turn can influence their evolutionary trajectories. In ectotherms like fishes, temperature is a particularly important environmental variable that is known to have significant impacts on the phenotype. Here, we raised specimens of the surface ecomorph of Astyanax mexicanus at temperatures of 20°C, 23°C, 25°C, and 28°C to examine how temperature influenced vertebral number and body shape. To increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 84 publications
(99 reference statements)
0
16
0
2
Order By: Relevance
“…We did not measure the number of skeletal elements, but assuming body shape and fin area are related to the number of vertebrae and fin rays, respectively, it seems likely that a slenderer body shape and a larger fin area would indicate a larger number of vertebrae and fin rays (cf. Aguirre et al 2019;Corral and Aguirre 2019), but this remains to be examined in the present case.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…We did not measure the number of skeletal elements, but assuming body shape and fin area are related to the number of vertebrae and fin rays, respectively, it seems likely that a slenderer body shape and a larger fin area would indicate a larger number of vertebrae and fin rays (cf. Aguirre et al 2019;Corral and Aguirre 2019), but this remains to be examined in the present case.…”
Section: Discussionmentioning
confidence: 81%
“…More recently, it was shown that counts of vertebrae and number of fin rays influence body shape and fin sizes as revealed for the genus Rhoadsia Fowler, 1911, which is endemic to western Ecuador and northwestern Peru (Aguirre et al 2019). Similarly, Mexican tetra (Astyanax mexicanus (De Filippi, 1853)) raised in 20 and 28°C water had a higher number of vertebrae and a more elongated body shape than fish raised at temperatures in between (Corral and Aguirre 2019). Environmental influence on body shape has also been shown for Chinook salmon (Oncorhynchus tshawytscha (Walbaum in Artedi, 1792)), where those from an ephemeral stream had deeper bodies than those that came from continuously Note: B is the regression coefficient; SE is the standard error; exp(B) is the odds ratio.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various body and skeletal deformities in fish have been reviewed in many publications [7][8][9][10][11][12][13][14][15][16]; earlier reports can also be found in Dawson's bibliographies [17][18][19][20]. Many of these deformities apparently can be treated as monstrosities, particularly when the vertebral column is shortened without pronounced curvature, resulting in an altered body form that is extremely short and deep.…”
Section: Introductionmentioning
confidence: 99%